30-Day Postoperative Complications After Surgical Treatment of Proximal Humerus Fractures: Reverse Total Shoulder Arthroplasty Versus Hemiarthroplasty. (3rd March 2023) - Khazzam, Michael; Ahn, Junho; Sager, Brian; Gates, Stephen; Sorich, Megan; Boes, Nathan
Abstract : Introduction: The purpose of this study was to evaluate risk factors associated with complications after reverse total shoulder arthroplasty (TSA) and hemiarthroplasty for the treatment of proximal humerus fractures. Methods: A retrospective review of the American College of Surgeons National Surgical Quality Improvement Program database was conducted. Current Procedural Terminology codes were used to identify patients treated for proximal humerus fracture with reverse TSA or hemiarthroplasty between 2005 and 2018. Results: One thousand five hundred sixty-three shoulder arthroplasties were conducted: 436 hemiarthroplasties and 1, 127 reverse TSA. The overall complication rate was 15.4% (15.7% reverse TSA; 14.7% hemiarthroplasty) ( P = 0.636). Most frequent complications included transfusion 11.1%, unplanned readmission 3.8%, and revision surgery 2.1%. A 1.1% incidence of thromboembolic events was noted. Complications occurred most frequently in patients older than 65 years; male; and patients with anemia, American Society of Anesthesiologists classification III-IV, inpatient procedure, bleeding disorders, duration of surgery >106 minutes, and length of stay >2.5 days. Patients with body mass index >36 kg/m 2 had a decreased risk of 30-day postoperative complications. Discussion: There was a 15.4% complication rate in the early postoperative period. In addition, no notable difference was found in complication rates between groups (hemiarthroplasty: 14.7%; reverse TSA 15.7%). Future studies are needed to determine whether there is a difference between these groups in the long-term outcome and survivorship of these implants.